2011
DOI: 10.1002/pro.707
|View full text |Cite
|
Sign up to set email alerts
|

GFP‐based evaluation system of recombinant expression through the secretory pathway in insect cells and its application to the extracellular domains of class C GPCRs

Abstract: Applications of the GFP-fusion technique have greatly facilitated evaluations of the amounts and qualities of sample proteins used for structural analyses. In this study, we applied the GFP-based sample evaluation to secreted protein expression by insect cells. We verified that a GFP variant, GFPuv, retains proper folding and monodispersity within all expression spaces in Sf9 cells, such as the cytosol, organelles, and even the extracellular space after secretion, and thus can serve as a proper folding reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 57 publications
0
28
0
Order By: Relevance
“…In this study, we identify a conserved surface during in vitro selection of human T1R2 for associating with T1R3. Identifying the dimerization surface of the sweet taste receptor was challenging due to low surface expression (2,38,39), which necessitated the selection of T1R2 mutants for enhanced surface expression and co-trafficking with T1R3. A subsequent deep mutational scan of T1R2 in human cells identified surfaces on lobe 1 of the LBD, on the CRD, and in TM6 for dimerization with T1R3 as assessed by their co-trafficking to the plasma membrane.…”
mentioning
confidence: 99%
“…In this study, we identify a conserved surface during in vitro selection of human T1R2 for associating with T1R3. Identifying the dimerization surface of the sweet taste receptor was challenging due to low surface expression (2,38,39), which necessitated the selection of T1R2 mutants for enhanced surface expression and co-trafficking with T1R3. A subsequent deep mutational scan of T1R2 in human cells identified surfaces on lobe 1 of the LBD, on the CRD, and in TM6 for dimerization with T1R3 as assessed by their co-trafficking to the plasma membrane.…”
mentioning
confidence: 99%
“…So far, not only the structural analyses but also the molecular functional analyses using the purified protein of T1rs have been completely hampered, due to the difficulties in the heterologous expression and purification even for the partial regions such as the LBD 19 . In this study, we found that the LBDs of T1r2 and T1r3 of medaka fish ( Oryzias latipes , also known as Japanese rice fish), a representative model organism in vertebrates, can be expressed heterologously as a properly folded and functional heterodimeric protein, thus enabling various biophysical analyses.…”
mentioning
confidence: 99%
“…We previously found that T1r2aLBD and T1r3LBD from medaka fish displayed favorable secreted expression and stable heterodimerization, although those from other sources, including mouse and human, displayed failure of folding and localization during the recombinant expression . To address the large‐scale preparation of the heterodimeric T1rLBD, we first attempted baculovirus expression, the most commonly used eukaryotic expression system for structural studies.…”
Section: Resultsmentioning
confidence: 99%